Młodzież akademicka wobec refleksji nad tożsamością = University students on their identity reflections - Turska, Elżbieta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
For university students, studying is not only the time of gaining knowledge and skills, but also an opportunity to develop one`s own personality. It is also the time to search for answers to identity questions. To be effective in an edukator`s work, apart from subject and methodological competence, it is very important to grasp who we are and to form a habit of continually reflecting upon oneself. The studied future educators appreciate the importance of reflecting on their own identity and see its profound sense.
Keywords: młodzież akademicka; studenci; tożsamość; refleksja